Persepsi Pasien tentang Tantangan Perawatan Luka Kronis Diabetes Melitus serta Implikasinya terhadap Kebutuhan Soft-skills Perawat - Cicilia Nony Ayuningsih Bratajaya; Ernawati Ernawati (Faletehan Health Journal, 2023)
The need of diabetic ulcer treatment was inline with the escalation of chronic wounds incidence in patients with diabetes mellitus. This study aimed to explore patients’ perception regarding nurses’ challenges to provide chronic diabetic wound care and the implications of the need of nurses’ soft-skills on it. This research was a phenomenological desciptive qualitative study with Colaizzi approach. The target population were diabetic clients who had wound care in the clinic within the last 6 months. The sampling technique was total sampling. 7 participants were interviewed. Besides suffering from diabetic ulcer, the participants realized that nurses faced various diabetic wound conditions, patients’ pain complaints, and challenges in performing wound care in which they had implication on the need for nurses’ soft skills. This study produced the theme of “the suffer of patients with diabetic chronic wound” with the subthemes of “wound pain”, “old wound cleansing”, “long recovery”, “doubts about healing”, “body image problem”, and “fear of amputation”. Meanwhile, on the theme of “challenges for wound nurses”, several sub-themes were emerged, namely: “wound conditions”, “patients’ complaints of pain”, and “the nature of wound care activities”. A humanist approach through the nurses' soft-skills could help patients and their families deal with chronic diabetic wounds to achieve an optimal wound healing.